PENGARUH PELAYANAN FISIOTERAPI BERBASIS COMPASSIONATE CARE TERHADAP PSYCHOLOGICAL READINESS TO RETURN TO SPORT PADA ATLET PASCA CEDERA ANTERIOR CRUCIATE LIGAMENT (ACL) - Sandi Akbar; Toto Marzuki; Azliyana Azizan; Siti Muawanah (JURNAL PROFESIONAL FISIOTERAPI, 2026)
Introduction: Anterior Cruciate Ligament (ACL) injury often delays athletes’ return to sport. Psychological Readiness to Return to Sport is a key factor in rehabilitation success. Compassionate Care, emphasizing empathy and emotional support, may enhance psychological readiness.To examine the effect of Compassionate Care-based physiotherapy on Psychological Readiness to Return to Sport among athletes following ACL injury. A quasi-experimental pretest-posttest control group study involved 60 athletes with ACL injury. The intervention group received Compassionate Care-based physiotherapy, while the control group received conventional physiotherapy for 12 weeks. Psychological readiness was assessed using the ACL-Return to Sport after Injury Scale (ACL-RSI). The intervention group showed significantly greater improvement in ACL-RSI scores than the control group (p<0.05). Confidence and motivation increased, while fear of reinjury decreased. Compassionate Care-based physiotherapy positively improves athletes’ psychological readiness to return to sport after ACL injury.